Simulation of charge transport in organic semiconductors: a time-dependent multiscale method based on nonequilibrium Green's functions - Leitherer, S.; Jäger, C.M.; Krause, A.; Halik, M.; Clark, T.; Thoss, M. (American Physical Society, 2017)
In weakly interacting organic semiconductors, static disorder and dynamic disorder often have an important impact on transport properties. Describing charge transport in these systems requires an approach that correctly takes structural and electronic fluctuations into account. Here, we present a multiscale method based on a combination of molecular-dynamics simulations, electronic-structure calculations, and a transport theory that uses time-dependent nonequilibrium Green’s functions. We apply the methodology to investigate charge transport in C60-containing self-assembled monolayers, which are used in organic field-effect transistors.